(untitled) (Regional aspects of productive forces development of Ukraine, 2022)
Introduction. Modern post-coronavirus conditions of economic development indicate that one of the strategic prospects for sustainable development of Ukraine’s regions is the further spread of the progressive global trend “Industry 4.0”, including industrial clusters. Clusters, as new forms of spatial organization of production, characterized by powerful mobilization opportunities and high competitiveness in global and national markets are recognized as important elements in the development of regional innovation ecosystems. They play an important role in promoting the shift and development of industrial parks. Therefore, cluster issues are relevant in all its manifestations, including at the level of research on the genesis of cluster theory from its inception to the formation of the modern (“classical”) variant. Purpose. The aim of the article is to analyse the genesis and evolution of the theory of economic clusters from the XVIII century (stage of origin, which is associated with the ideas of J. Tunen) and the 90s of XX century (emergence of modern cluster theory – M. Porter). Research methods. The article used the historical method, logical-abstract, methods of analysis and synthesis. Results. The article emphasizes that the concept of “cluster” is inherent not only in economics. A thorough analysis of economic scientific sources gives grounds to claim that the first developments in cluster theory can be traced in the works of economists of various fields and schools. However, most researchers believe that the founders of cluster theory were J. Tunen and A. Marshall. In its modern form, cluster theory began to take shape in the 80’s and 90’s of the XX century. The ancestor of cluster theory is considered to be the famous American scientist M. Porter. It was found that M. Porter in his research uses several approaches to the interpretation of the concept of “cluster” – geographical, network, synergistic and so on. Встановлено, що сутність і зміст теорії кластерів М. Портер розкриває через модель «Алмаз», яка включає чотири взаємопов’язані компоненти: факторні умови; стан попиту; суміжні та допоміжні галузі (кластери); стратегія, структура і суперництво фірми. Визначено, що на розвиток промислових кластерів (за М. Портером) значний вплив мають державний і приватний сектори, соціальна структура, ініціативи, пов’язані з діяльністю промислового кластера. Визначено переваги та недоліки кластерної теорії П. Портера та розроблено модель промислового кластера. Висновок. Аналіз показує, що кластерні ідеї серед науковців зустрічаються практично в усіх економічних напрямах і школах, незалежно від історичного періоду їх існування. Про переваги такої форми об’єднання було відомо ще на початку ХХ ст. Встановлено, що засновник сучасної кластерної теорії М. Портер під час її створення на основі концепції конкурентної переваги породив різні підходи та теоретичні досягнення економічної наукової думки (насамперед просторову, інноваційну та мережеву наукові теорії). Важливим аспектом промислово-кластерної моделі М. Портера є синергетичний ефект, в основі якого промислові кластери економічними засобами (продуктивність, інновації, створення нового бізнесу) впливають на конкурентоспроможність, що в кінцевому результаті забезпечує розвиток економіки держави.